A Fast and Scalable Pre-Lithiation Approach for Practical Large-Capacity Lithium-Ion Capacitors. Issue 11 (22nd November 2021) - Sun, Xianzhong; Wang, Penglei; An, Yabin; Zhang, Xiong; Zheng, Shuanghao; Wang, Kai; Ma, Yanwei
Abstract : Lithium-ion capacitors (LICs) bridge the gap between lithium-ion batteries (LIBs) and electrical double-layer capacitors (EDLCs) owing to their unique energy storage mechanisms. From the viewpoints of electrode materials and cell design, the pre-lithiation process is indispensable for improving the working voltage and energy density of LICs. However, the conventional physical short-circuit (PSC) method is time-consuming, which limits the mass-production of practical large-capacity LIC cells. Three alternative pre-lithiation protocols have been proposed, combining the PSC protocol and electrochemical approaches to shorten the pre-lithiation time. The prototype LIC pre-lithiated by using the open-circuit potential cycling (OPC) protocol has the lowest internal resistance and superior high-rate capability (even at 200C-rate). The 900-F large-capacity laminated LIC cells have been assembled and pre-lithiated to validate the feasibility of this method. The pre-lithiation time has been reduced from 470 h (PSC protocol) to 19 h (OPC protocol). This combined protocol is presumed to counteract the voltage loss and enhance the Li + ion diffusion between multiple anode electrodes during the pre-lithiation process.